Cognitive Training: Transfer Beyond the Laboratory?. (May 2021) - Lintern, Gavan; Boot, Walter R.
Objective: To assess the evidence of general transfer from training on abstract computer-based exercises and video games to driving and flight control. Background: Many believe that training on abstract computer-based exercises and video games enhances cognitive capacities to the benefit of performance in operational contexts. The basic research in this area is controversial. Method: We summarize reviews of the basic research data on transfer from training on abstract computer-based exercises and video games and undertake a detailed methodological review of flight and driving transfer studies. Results: Reviews of basic transfer research fail to reveal evidence of general transfer, although a few applied studies are said to show general transfer to driving or flight control. Our review of these applied studies identifies issues with research methods and data interpretation that compromise the credibility of their results to an extent that they do not provide robust evidence of general transfer from abstract computer-based exercises or video games. Conclusion: The state of cognitive training and video game training in relation to transfer has failed to meet early expectations. Much of the research in this area suffers from inadequate experimental control and flawed interpretation of results. We call for adherence to robust experimental design, critical evaluation of data patterns, and replication of keystone results. We also call for a theoretically grounded research effort, and we outline relevant theoretical conceptions of transfer. Application: A robust theory of transfer and better understanding of transfer effects can guide development of principles for design and use of training simulators.